Photodetectors: High‐Performance Transition Metal Dichalcogenide Photodetectors Enhanced by Self‐Assembled Monolayer Doping (Adv. Funct. Mater. 27/2015). (14th July 2015) - Kang, Dong‐Ho; Kim, Myung‐Soo; Shim, Jaewoo; Jeon, Jeaho; Park, Hyung‐Youl; Jung, Woo‐Shik; Yu, Hyun‐Yong; Pang, Chang‐Hyun; Lee, Sungjoo; Park, Jin‐Hong
Abstract : High‐performance transition metal dichalcogenide photo–detectors are enhanced by self‐assembled mono‐layer (SAM) doping. On page 4219, J.‐H. Park and colleagues show how the photoresponsivity of WSe2 and MoS2 photodetectors is dramatically improved as a result of the enhancement of transition metal dichalcogenides optical properties by SAM doping. This is also investigated in detail through photoluminescence analysis.